2020
DOI: 10.18632/aging.103730
|View full text |Cite|
|
Sign up to set email alerts
|

Taurine suppresses ROS-dependent autophagy via activating Akt/mTOR signaling pathway in calcium oxalate crystals-induced renal tubular epithelial cell injury

Abstract: Oxidative stress and autophagy are the key promoters of calcium oxalate (CaOx) nephrolithiasis. Taurine is an antioxidant that plays a protective role in the pathogenesis of kidney disease. Previous studies found that taurine suppressed cellular oxidative stress, and inhibited autophagy activation. However, the effect of taurine on CaOx kidney stone formation remains unknown. In the present work, we explored the regulatory effects of taurine on CaOx crystals-induced HK-2 cell injury. Results showed that pretre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…In another study, estrogen/estrogen receptor beta (ERβ) exerted protective effect on renal CaOx crystal formation by inhibiting liver oxalate biosynthesis and reducing the expression of NADPH oxidase subunit 2 (NOX2) 36 . Sun et al reported pretreatment with taurine markedly reduced oxidative stress by promoting SOD2 activity and decreasing MDA concentration, and also suppressed ROS-dependent autophagy through activating Akt/mTOR pathway, thus alleviating crystal-induced oxidative injury in kidney tissues and HK-2 cells 37 . Liu et al described the complete role of inflammatory pyroptotic in the CaOx crystal-triggered tubular cell damage, and H3 relaxin supplementation provided direct treatment for this particular form of inflammatory injury in crystalline nephropathies via the ATP-depleted protection 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, estrogen/estrogen receptor beta (ERβ) exerted protective effect on renal CaOx crystal formation by inhibiting liver oxalate biosynthesis and reducing the expression of NADPH oxidase subunit 2 (NOX2) 36 . Sun et al reported pretreatment with taurine markedly reduced oxidative stress by promoting SOD2 activity and decreasing MDA concentration, and also suppressed ROS-dependent autophagy through activating Akt/mTOR pathway, thus alleviating crystal-induced oxidative injury in kidney tissues and HK-2 cells 37 . Liu et al described the complete role of inflammatory pyroptotic in the CaOx crystal-triggered tubular cell damage, and H3 relaxin supplementation provided direct treatment for this particular form of inflammatory injury in crystalline nephropathies via the ATP-depleted protection 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Zhai et al ( 53 ) have proved that overexpressed SIRT1 increases the phosphorylation levels of PI3K and AKT, thereby inhibiting the apoptosis of cardiomyocytes induced by high glucose and reducing its oxidative stress response. MTOR is an important downstream target of AKT and takes part in the expression and transcription of related proteins and genes, thus affecting biological activities such as inflammation, oxidative stress, apoptosis, and so on ( 54 , 55 ). The over-expressed SIRT1 activates PI3K through tyrosine kinase receptor, then the activated PI3K promotes the phosphorylation of AKT, activates MTOR, and inhibits oxidative stress and inflammation ( 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, extensive research has explored the effectiveness of generic antioxidants and plant extracts on the alleviation of CaOx crystal damage to epithelial cells, among others L-arginine [46], vitamin E [46], theaflavin [54], taurine [55], corn silk polysaccharides [56], polysaccharides from green seaweed [57], aspidopterys obcordata [58], terminalia arjuna [59], etc. Studies showed that the effects of these antioxidants were beneficial for alleviating oxidative stress on epithelial cells by reducing markers of oxidative damage and increasing cell viability.…”
Section: Antioxidants/plant Extractsmentioning
confidence: 99%
“…For some, the underlying mechanisms of these effects have been established. Theaflavin effects are mediated via the miR-128-3p/SIRT1 axis [54], taurine inhibition of ROS-dependent autophagy is facilitated by activating the Akt/mTOR signaling pathway [55], while TGAME (plant metabolite 3,4,5-tri-O-galloylquinic acid methyl ester) decreases annexin A1 cell surface expression [60]. Further research is needed in order to determine mechanisms of action for other antioxidants and plant extracts, and whether there are other pathways present apart from free radical scavenging.…”
Section: Antioxidants/plant Extractsmentioning
confidence: 99%